Single‐Crystalline‐Phase Mo3VOx: An Efficient Catalyst for the Partial Oxidation of Acrolein to Acrylic Acid. Issue 10 (21st June 2013) - Chen, Chen; Kosuke, Nakatani; Murayama, Toru; Ueda, Wataru
<x xml:space="preserve">Abstract</x> Being single (crystalline): Four single‐crystalline‐phase Mo3VOx materials are utilized as catalysts for the partial oxidation of acrolein to acrylic acid. The crystalline structure has a clear effect on catalytic performance. Mo3VOx with a trigonal crystalline structure is the most efficient catalyst: 99.8 % conversion with 93.9 % selectivity for acrylic acid is obtained at a temperature (217.3 °C) much lower than that previously reported.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>